Closed treatment of both bone of forearm fractures in children: study of radiological and functional assessment at maturity - Din, Mohd Hadizie (2013)
Forearm fractures Although closed reduction and casting is the preferred treatment, the outcomes remain variable. The purpose of this study was to evaluate the outcome of the forearm fractures among the children who had been treated with closed reduction and cast. It also studied whether age of patient at time of fracture, angulation of radius and ulna, forearm rotational limitation or location of fractures influence the functional outcome. Fourty four children who had arrived at skeletal maturity which is minimally 14 years old for the girls and 16 years old for the boys, involved in this study. All of them had at least 4 years of remaining growth at the time of fracture. They have been selected and contacted after reviewing their radiological and treatment records and have been asked to come to HUSM for further evaluation. During evaluation, the functional ability of the involved hand and forearm has been assessed. A radiological assessment of affected limb has been performed through a proper antero- posterior and lateral radiograph. The functional outcome was assessed based on activity of daily living, the differences of the pronation and supination of the affected forearm with the normal arm and graded using Price method into excellent, good, poor and fair outcome. The angulations of the radius and ulna post reduction and at skeletal maturity were documented. Data was statistically analysed using SPSS version 20. Thirty- six male and 8 female were involved in this study. The age at time of fracture was within 5 to 12 years old with the mean of 6 years old. Majority sustained injury at middle third (20 patients) and distal third (23 patients) forearm. There was significant improvement of angulation at skeletal maturity compared to post reduction angulation (p<0.001). Initial mean angulation for radius was 10.27° (3° - 24°) and 2.84° (0°- 11°) at skeletal maturity. The initial mean for ulna angulation was 8.93° (1°-19°) and 2.27° (0°'8°) at skeletal maturity. 88.6% had excellent outcome and only 11.4% had good outcome. There was no poor or fair outcome in this study. Only age at time of fracture had significant association with outcome (Multiple logistic regression, p= 1.194; adjusted odds ratio, OR= 3.299; 95% CI= 1.096, 9.930; p-value= 0.034). This study has shown that in children less than 12 years old with initial angulation of less than 10.27° for radius and less than 8.93° for ulna, 88.6% will have an excellent functional outcome. Apart from that, remodeling of 72.3% for radius and 74.6% for ulna can be expected from the time of reduction until the patients has reached their skeletal maturity. Among the angulation of fracture, age at time of fracture, limitation of forearm rotation and location of fracture, only age at time of fracture influences the functional outcome.